ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢çš„å¦ç”Ÿ ä½¿ç”¨æ—¶é—´å‰¯è¯â€œæ›¾ç»â€å’Œâ€œå·²ç»â€çš„æŽŒæ¡æƒ…å†µåˆ†æž - Novita, Lyan Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
?? ?????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????2014????????????????????????????????????????????????????????2014????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????   ???? ?? ?? ???? Abstract Adverbs are an important part of grammar, ?Ceng Jing? and ?Yi Jing? belong to time adverbs.?Ceng Jing? and ?Yi Jing? have shown that the action or the emergence of the state should be earlier than a certain time, and sometimes can be replaced. Therefore, Chinese learners are prone to misunderstandings of the two words, confusion of usage, indiscriminate use, misuse and improper use of the situation. In order to understand the mastery and difficulty of of the students of Mandarin at Tanjungpura University, year of enrollment 2014 against  "Ceng Jing" and "Yi Jing",were tested by literature research and test. Test results show that students of Mandarin at Tanjungpura University, year of enrollment 2014 to do the identification of "Ceng Jing" and "Yi Jing" "words and words on the incorrect part of the position is not very good. In the right place part of the word where the student is wrong is in the word order. This shows that the students of the school against"Ceng Jing" and "Yi Jing" to grasp the situation is not particularly good, and "Yi Jing" is better than "Ceng Jing". The author of the test results, put forward the corresponding teaching strategies. Keywords: The Condition of Students Understanding ?Ceng Jing? and ?Yi Jing?